Tổng hợp hydrotalxit mang stearat và ứng dụng trong lớp phủ epoxy để bảo vệ chống ăn mòn cho thép cacbon - Dương, Nguyễn Thùy; Trước, Bùi Văn; Thủy, Thái Thu; Xuân Hằng, Tô Thị; Trúc, Trịnh Anh (Vietnam Journal of Chemistry, 2015)
Hydrotalcite containing stearate (HT-SA) was prepared using the co-precipitation method. The HT-SA obtained was characterized by Fourier transform infrared spectroscopy (FT-IR), thermal gravimetric analysis (TGA). The results showed that the stearate is present in hydrotalcite (about 26.5 %). The inhibitive efficiency of HT-SA on carbon steel was characterized by electrochemical method and the protective properties of the epoxy coating containing HT-SA were evaluated by electrochemical impedance spectroscopy (EIS). The obtained results showed that the HT-SA is an anodic inhibitor. Its efficiency was about 74 % at a concentration of 3 g/l. The presence of HT-SA (3 %) improved the barrier properties and corrosion protection of the epoxy coating.